Professionalism in teaching: A survey study on Afghan EFL educators’ professional development needs - Samim, Khalid Ahmad (Goodwood Publishing, 2025)
Purpose: The purpose of this study was to explore the perceived professional development needs of Afghan EFL educators and identify the areas of teaching in which they prioritize to be developed professionally. Methodology/approach: A quantitative survey design was employed to discover EFL teachers’ PD needs. 25 English educators majoring in the TESOL graduate program at Kabul Education University were selected purposively. The data were collected through a questionnaire, and was analyzed using SPSS for more comprehensive results. Results/findings: The overall results regarding PD needs of Afghan EFL educators indicate that they are generally in need of lesson planning and curriculum development, up-to-date methodologies and differentiated instructions, technology-integrated instruction, reflective practices, and assessment and evaluation techniques. Conclusion: The study concludes that designing PD programs based on teachers’ actual needs is crucial to improving teaching competence. Context-specific and needs-based PD programs can enhance instructional quality and student learning outcomes in Afghanistan’s EFL context. Limitations: Limited sample size, absence of female participants, and randomization could be listed as limitation of the study. Contribution: By identifying the PD needs of Afghan EFL educators, the study can contribute the designers of targeted training programs that aim to enhance teaching quality and effectiveness.